Methodologies of Application of Sol-Gel Based Solution onto Substrate: A Review - Bera, Saheli; Udayabhanu, G.; Narayan, Ramanuj; Rout, Tapan K. (Journal of Coating Science and Technology, 2016)
Just as the diverse as the various substrates that can be coated is the choice of several coating methods by which the coating can be applied to these pretreated surfaces. They include the manual methods, where great skills and experience is needed, on the other hand there are automated and robotics coating control methods where coating can be applied with more precise manner. Sol-gel process is one of the promising bottom up nano-coating technologies to develop thin film over various metallic substrates. The property and characteristic of the resulting film is strongly influenced by the various parameters and reaction conditions of the sol-gel process and of course on the deposition techniques. In this review, we have thrown some lights on different coating application processes covering theoretical principle, advantages, disadvantages, and special various parameters controlling the final film quality.